Studi Pengetahuan, Sikap dan Motivasi Pekerja terhadap Pemakaian Alat Pelindung Diri (APD) pada Driver Alat Berat di PT. Antam Tbk UBPN Kolaka - Windi Astuti; Ramadhan Tosepu; La Ode Liaumin Azim; Syawal K. Saptaputra; Farit Rezal; Indah Ade Prianti (Jurnal Kendari Kesehatan Masyarakat, 2025)
This study focuses on the use of Personal Protective Equipment (PPE) by heavy equipment drivers at PT. Antam Tbk. UBPN Kolaka. The aim is to analyze the relationship between knowledge, attitude, and motivation with PPE usage behavior in 2024. The research method used is a quantitative approach with a cross-sectional design. This study involved 135 respondents selected through total sampling. The independent variable analyzed is PPE usage behavior, while the dependent variables include knowledge, attitude, and worker motivation. Data were collected through questionnaires that had been tested for validity and reliability, and analyzed using SPSS with a chi-square test. The results showed a significant relationship between knowledge, attitude, and motivation with PPE usage behavior. Additionally, the study found that these factors play an important role in shaping safety behavior in the workplace. The study emphasizes the importance of PPE usage by heavy equipment drivers to enhance work safety and productivity. It is hoped that the results of this study can serve as a basis for the company in designing more effective training and socialization programs related to PPE usage